The evolution of international logistics in the era of globalisation: opportunities and challenges for business operations - Kabanova, Olena; Popel, Serhii Anatoliiovych; Kopylova, Olha; Piriashvili, Oleksandr (Technical University of Košice, Košice, Slovak Republic, 2025)
The state of international logistics is closely related to political, economic, and technological changes that take place in the context of dynamic technological development, military threats, and, at the same time, integration of countries in search of partners. The article aims to highlight the main aspects and features of the international logistic development in the globalization context. The methodology included general scientific methods of studying the chosen research object (analysis, synthesis, grouping). The logistics productivity index is considered the leading indicator of the global logistics sector developmet in 2018-2023. The study’s results demonstrate the dependence of logistics development on several factors. In the leading countries, according to the Logistics Performance Index, the drivers of change are investments in infrastructure, transport networks, IT communications, technology, digital networks, logistics centres and hubs; logistics education and competence; government support and incentives for the sector; and a stable political and economic environment that fosters investment and innovation. The article highlights the main aspects and features of the international logistics development in globalization condition. The practical value ofthe study lies in highlighting the challenges faced by the logistics sector on a global scale in the context of technological shifts and military threats (the need for investment in maintaining logistics sustainability, changing supply chains, and rising delivery costs).
Keywords: international logistics; logistics performance; globalization; logistics operations; international trade; міжнародна логістика; логістична ефективність; глобалізація; логістичні операції; міжнародна торгівля